Pengembangan Aplikasi Perangkat Bergerak Berlangganan Katering Daring - Brilliant Richky Setya Putra; Agi Putra Kharisma; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
COVID-19 affects consumers' lifestyles, especially in ordering food online. Ordering food online is like using an online food ordering service application. The obstacle faced by this lifestyle is the wastage of food costs. Another obstacle is that there are consumers who do not have time to prepare food independently in order to reduce costs. This can be accomplished with alternatives such as daily meal ordering which prepares scheduled breakfast and lunch at affordable prices. Therefore we need a system that can help bring together daily catering providers and their customers. The system that is built must have high mobility so that it has easy access. In this study, two Android-based applications that are integrated with each other will be built. Determination of functional requirements or application features applying the Minimum Viable Product (MVP) methodology. The development flow follows the Software Development Life Cycle (SDLC) Waterfall. Functional requirements testing using the black box testing method with validation testing techniques. Non-functional testing using the System Usability Scale (SUS) questionnaire method produces an average SUS scale value of 80.5 for usability in customer applications and 66 for usability in vendor applications. With this application, it can help connect daily catering providers with customers in an efficient and integrated manner.